Evolution of mechanical properties of kerogen with thermal maturity. (November 2022) - Wang, Jianfeng; Liu, Yuke; Yang, Chao; Jiang, Wenmin; Li, Yun; Xiong, Yongqiang; Peng, Ping'an
Abstract: Kerogen is the most abundant form of naturally occurring organic matter in organic-rich shale, and it can affect the macro-mechanical characteristics of shale reservoirs during the whole shale thermal evolution process. However, the magnitude and mechanism of this effect are not clear. Here, a relatively low-maturity kerogen isolated from an organic-rich shale was used to prepare a series of kerogen samples of different maturities in an artificial pyrolysis experiment. Raman spectroscopy and solid-state 13 C nuclear magnetic resonance (NMR) spectroscopy were used to determine changes in the chemical structures of the kerogen samples, and in situ nanoindentation analysis was employed to characterize the evolution of their mechanical properties. Raman spectral analyses indicate that Raman band separation (RBS) is very sensitive to thermal maturity, increasing with maturity and displaying a strong linear correlation with mechanical properties of kerogen such as hardness and Young's modulus. Based on the solid-state 13 C NMR and nanoindentation analysis, the evolution of kerogen mechanical properties with maturity can be divided into two stages: oil-generation wet-gas stage (corresponding to 0.7%–2.5% EasyRo), and dry-gas stage (2.5%–4.5% EasyRo). In the former, kerogen exhibits a soft nature with relatively low hardness and Young's modulus, possibly attributable to its relatively large proportion of aliphatic carbon and long-chain alkanes. When maturity reaches the gas stage, kerogen becomes increasingly stiff due to the markedly increased proportion of aromatic and bridgehead carbon. Considering the strong positive correlation between mechanical parameters and chemical-structure parameters (RBS, and aromatic and bridgehead carbon ratios) of kerogen during the overall thermal evolution process, we suggest that the stiffening of kerogen may result from the decreasing content of aliphatic chains and increasing aromatic carbon. This study will be beneficial to the development of rock mechanical models that are critical for accurately evaluating borehole stability and optimizing hydraulic fracture design. Highlights: Kerogen mechanical properties evolution with maturity is divided into two stages. Hardness and Young's modulus of kerogen increase with thermal maturity. Kerogen mechanical parameter is closely related to chemical-structure parameter. Condensation of aromatic groups controls kerogen mechanical properties evolution.